RNF5: inhibiting antiviral immunity and shaping virus life cycle - Ge, Junyi; Zhang, Leiliang (Frontiers in Immunology, 2024)
RNF5 is an E3 ubiquitin ligase involved in various physiological processes such as protein localization and cancer progression. Recent studies have shown that RNF5 significantly inhibits antiviral innate immunity by promoting the ubiquitination and degradation of STING and MAVS, which are essential adaptor proteins, as well as their downstream signal IRF3. The abundance of RNF5 is delicately regulated by both host factors and viruses. Host factors have been found to restrict RNF5-mediated ubiquitination, maintaining the stability of STING or MAVS through distinct mechanisms. Meanwhile, viruses have developed ingenious strategies to hijack RNF5 to ubiquitinate and degrade immune proteins. Moreover, recent studies have revealed the multifaceted roles of RNF5 in the life cycle of various viruses, including SARS-CoV-2 and KSHV. Based on these emerging discoveries, RNF5 represents a novel means of modulating antiviral immunity. In this review, we summarize the latest research on the roles of RNF5 in antiviral immunity and virus life cycle. This comprehensive understanding could offer valuable insights into exploring potential therapeutic applications focused on targeting RNF5 during viral infections.